The ability of chitosan–stearin as an edible coating on the quality of broiler chicken meat during cold storage. - Yunilas, Yunilas; Hasanah, Uswatun; Purnawarman, Trioso; Nasution, Muheri Indra Aja (Journal of Advanced Veterinary and Animal Research, 2025)
Objective: This study aimed to evaluate how well fresh broiler meat may be preserved in cold storage using chitosan–stearin as an edible coating. Materials and Methods: A completely randomized design with a 3 x 5 factorial arrangement and three replications was employed. Factor I represented the formula dosage (FD) (FD0 = 0% chitosan + 0% stearin; FD1 = 1.5% chitosan + 1% stearin; FD2 = 3% chitosan + 1% stearin), while Factor II represented storage time (ST) (ST0 = 0 days; ST1 = 3 days; ST2 = 6 days; ST3 = 9 days; ST4 = 12 days). Results: The results showed that the water content, cooking loss, protein content, and fat content of broiler meat were significantly affected (p < 0.01) by the FD and ST. Nonetheless, no significant difference (p > 0.05) was observed in the meat’s ability to hold water. The broiler meat’s pH was significantly affected (p < 0.01) by the FD, but it was not significantly affected (p > 0.05) by the ST. Furthermore, no treatment underwent testing, which revealed the presence of Escherichia coli and Salmonella sp. Conclusion: Chitosan–stearin edible coatings with different formula doses FD and ST consistently preserve the quality of fresh broiler meat during cold storage, with average values of water content ranging from 48.97% to 53.73%, water-holding capacity from 17.52% to 34.30%, cooking loss from 10.03% to 33.19%, pH levels from 4.93 to 5.53, protein content from 14.54% to 17.46%, fat content from 20.55% to 24.21%, and no detectable presence of E. coli and Salmonella sp. J. Adv. Vet. Anim. Res., 12(1): 99–105, March 2025 http://doi.org/10.5455/javar.2025.l876